1997
DOI: 10.3183/npprj-1997-12-04-p260-266
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of a rosin sizing agent in paper by means of EPMA, ESCA and TOF-SIMS

Abstract: EPMA(e1ectronprobe micro analysis), ESCA (electron spectroscopy for chemical analysis) and TOF-SIMS (time of flight type secondary ion mass spectrometry) were used to detect the distribution of a rosin sizing agent in paper. For EPMA we labelled paper samples with osmium tetroxide which enabled the detection of rosin in the XY direction of the paper sheet. For ESCA we labelled paper samples with fluorine which also enabled the detection of rosin. At the same time, the ESCA angle-dependent technique was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…On a micrometer scale, various studies have shown non-uniformity in the surface distribution of sizing agents. Such observations have been reported especially in the case of rosin sizing (Davison 1975;Strazdins 1981;Ozaki and Sawatari 1997;Wang et al 2000), and excessively non-uniform coverage has been correlated to inefficient sizing (Lee 1936;Strazdins 1981). In the early work by Lee (1936) the most efficient sizing with rosin soap was achieved when the size particles were the smallest, achieving a better distribution.…”
Section: It Doesn't Have To Be Uniformmentioning
confidence: 88%
See 1 more Smart Citation
“…On a micrometer scale, various studies have shown non-uniformity in the surface distribution of sizing agents. Such observations have been reported especially in the case of rosin sizing (Davison 1975;Strazdins 1981;Ozaki and Sawatari 1997;Wang et al 2000), and excessively non-uniform coverage has been correlated to inefficient sizing (Lee 1936;Strazdins 1981). In the early work by Lee (1936) the most efficient sizing with rosin soap was achieved when the size particles were the smallest, achieving a better distribution.…”
Section: It Doesn't Have To Be Uniformmentioning
confidence: 88%
“…In the early work by Lee (1936) the most efficient sizing with rosin soap was achieved when the size particles were the smallest, achieving a better distribution. More recent work shows, however, that microscopic studies may miss an important part of the story; Ozaki and Sawatari (1997), using electron probe microanalysis (EPMA), detected an uneven distribution of rosin. However, the same samples, when studied by time-of-flight surface ionization mass spectroscopy (TOF-SIMS) ncsu.edu/bioresources .…”
Section: It Doesn't Have To Be Uniformmentioning
confidence: 99%
“…The fixation of the rosin onto paper surface has not yet been clearly established. However, the distribution of rosin on the surface layer of paper has been demonstrated by the use of three analytical techniques: EPMA, ESCA, and TOF-SIMS [1]. Results from that study showed that rosin is distributed considerably evenly on the outermost surface of paper.…”
Section: Introductionmentioning
confidence: 83%
“…The surface modification of paper by nitrogen plasma treatment was detected by comparison of the systematic changes in the intensities of various mass peaks using ToF-SIMS (Deslandes et al 1998). Other chemical agents, such as cationic starch adsorbed on pulp and sizing agent distributed in paper sheets, were all able to be determined by ToF-SIMS (Ozaki and Sawatari 1998;Matsushita et al 2008). The visualized surface distribution of chemical agents on pulp and paper can be obtained by ToF-SIMS images.…”
Section: Surface Chemical Compositional Analysis Of Pulp and Papermentioning
confidence: 99%